Inspiration of Astronomy in the movies: a history of a close encounter - Garcia, Beatriz Elena (2012)
The connection between astronomy and an independent, widespread cultural expression like cinematography is of particular interest within the context of the Inspiration of Astronomical Phenomena. Astronomy has caught the interest of the seventh art since its birth, early in the twentieth century. In this paper we go through a collection of movies that reveal how astronomy and astronomers are perceived by society. We notice the influence of the progress achieved in astronautics in the second half of the past century, and how interplanetary or even intergalactic travels have become a recurrent issue. In many cases, astronomical facts are rigorously treated, but several other times, serious mistakes are transmitted. Biographical movies based on astronomical celebrities are rare, but some are masterpieces, like Giordano Bruno by Giuliano Montaldo, or Galileo Galilei by Liliana Cavani. In this sense the astronomers, as main characters in cinema, support the idea of the scientist as everyman, connected with life and, in many cases, with a sense of social responsibility. From the analysis of more than a hundred movies, we can see that this particular manifestation of art, which involves science and technology, can be used not only to reproduce astronomical events, transmit a message or reproduce a particular epoch of science history, but also to teach, to develop a critical faculty when faced with information from the media, and to show that astronomical facts can be as interesting, relevant, dramatic, happy or funny as real life.